Case Report: Delayed Primary Wound Closure After Extensive Abdominal Wall Resection for Infection and Malignancy Using TopClosure® - Solomonov, Evgeny; Khalifa, Muhammad; Rozentsvaig, Vladimir; Koifman, Itzhak; Biswas, Seema; Topaz, Moris (Frontiers in Surgery, 2021)
The closure of a massive abdominal wall defect is illustrated using a novel dynamic closure technique - the TopClosure® tension relief system. This system attaches to the abdominal wall immediately after laparotomy and allows for early approximation of the skin, avoiding an open abdomen and the complications associated with this. The technique in this case was employed after extensive resection of the abdominal wall for infected skin metastases of colonic adenocarcinoma and circumvented postoperative ventilation and open abdomen. Early recovery after such extensive surgery is important in terms of patient morbidity and mortality. In this case, primary surgery may not have been an acceptable risk to undertake without the option of Top Closure of the abdomen. We illustrate the technique of abdominal wall closure through a series of images of the procedure.